Internet of Things Application in Monitoring Sick Building Syndrome - Keshihakumar Kalaithasan; N. A. M. Radzi; H. Z. Abidin (Indonesian Journal of Electrical Engineering and Computer Science, 2018)
Sick Building Syndrome (SBS) is a health condition whereby a patient is presented with either vague temporary symptoms such as fatigue, aches and sensitivity to odour or more significant temporary symptoms such as itchy eyes, skin rashes and nasal allergy when they are in a building. Numerous factors have been associated with SBS, but the lack of an accurate diagnosis for these symptoms make treatment more difficult, as risk of treating the patient with wrong diagnosis is relative when the cause root is not known. Thus, taking a preventive approach is a more viable solution to the problem. In this paper, a simple, mobile and cost efficient Internet of Things (IoT) based SBS system is proposed. The system is built using Raspberry Pi minicomputer that would then be integrated with an IoT middleware. The middleware would enable the user to monitor parameters that are to be tested; which are temperature, humidity, light, sound and dust. Three IoT middleware are used to evaluate which one works best for the SBS system proposed. The combination of recorded sensor data would then be used to determine whether or not the building is causing SBS to the occupant. The studies show that FavorIoT platform is the most suitable IoT platform to be used with the SBS system and the system has successfully identified whether or not a building is causing SBS.